(untitled) (Research, Society and Development, 2021)
The externalization of internal organs in fish has been recorded over time in the scientific literature. Most of the records are related to the eversion or protrusion of the stomach and /or intestine, mainly due to barotrauma. However, a small portion of the records refer to several natural causes. The present study aimed to record the occurrence of a rare event of vaginal eversion in the spiny dwarf ray Psammobatis rutrum. On 06/15/2020 three specimens (2 females and 1 male) were captured as bycatch pair trawl in Barra de Santos SP, with an average depth of 27 meters. Among them, a female specimen presented a protrusion via the cloacal opening. Through necropsy, comparative evaluation and study of the reproductive pathways it was identified that the externalized organ was the vaginal wall. Although there are many records of externalization of Elasmobranchii organs, mainly related to the natural eversion behavior of the stomach and intestine, only one record of this type of event has been reported for the reproductive organ. It was not possible to identify the cause of vaginal eversion, but this event is associated with a pelvic prolapse, which may have been intensified by natural causes or due to capture.